Optimization of Whatsapp Social Media by Bhabinkamtibmas to Prevent Theft Cases at the Bandarlampung Police - Rizky Prawira (Indonesian Journal of Police Studies, 2021)
This problem arises in the background by the theft case in the city of Bandar Lampung. With an approach with the community through binluh by conveying security and security messages, especially in preventing theft by using the Whatsapp application carried out by bhabinkamtibmas. This study aims to optimize the use of Whatsapp as a communication medium by bhabinkamtibmas in carrying out their duties, as well as factors that influence the use of Whatsapp which require a system or mechanism to facilitate the task of bhabinkamtibmas. Concepts and theories to analyze the research focus. The research concept includes communication media, Whatsapp is used to prevent theft, bhabinkamtibmas in conveying messages, the concept of prevention, the concept of theft, Perkap Number 21 of 2007, Perkap Number 3 of 2015. Theories include Prevention Theory and Communication Theory. The research method systematically is a qualitative approach. This type of research is descriptive analytic. Primary and secondary data sources. Data collection techniques with Interview, Observation, and Document Review. The location is in the Binmas Unit Polresta Bandar Lampung. Validity by triangulation. Data analysis using interactive analysis models. The results of the study found that the use of Whatsapp which was analyzed with articles 9 and 10 of Perkap No. 21 of 2007 and Perkap No. 3 of 2015. The prevention of theft can be done with a prevention approach and the implementation of bhabinkamtibmas duties in accordance with competence. The conclusion of the optimization of Whatsapp social media by bhabinkamtibmas to prevent theft cases can be run optimally. Constructive suggestions include suggestions for further optimizing the implementation of the use of Whatsapp for conveying messages on theft prevention to the public as well as communicating with prevention which can be done primary, secondary or tertiary.